Trends in chronic kidney disease-related mortality among older adults in the United States from 1999-2020 - Hamza Ehtesham; Ahmed Kamal Siddiqi; Marium Omair Mirza; Mushtaq Ahmad; Rija Shakil (Archives of Gerontology and Geriatrics Plus)
Background: With increasing age in the United States, the disease burden of chronic kidney disease (CKD) has increased. The CKD-related mortality trends have not been explored for individuals aged ≥ 65 years. The aim of the study was to identify and evaluate the trends in sex, race, and region among CKD-related mortality in older adults. Methods: Death records sourced from the CDC WONDER (Centers for Disease Control and Prevention Wide-Ranging Online Data for Epidemiologic Research) database were used to analyze mortality trends of CKD in individuals aged ≥65 years from 1999 to 2020. We computed age-adjusted mortality rates (AAMRs) per 100,000 population and annual percent changes (APC) using Joinpoint software. The analysis was structured according to year, sex, race/ethnicity, and geographical regions. Results: From 1999 to 2020, there were 1,572,057 CKD-related deaths. The age-adjusted mortality rate (AAMR) rose from 1999 to 2005, declined until 2009, surged from 2009 to 2012, fell in 2015, and increased again in 2020. Men had a higher AAMR (225) than women (136.3). Non-Hispanic Black or African Americans experienced the highest AAMR (319.2), followed by NH American Indian or Alaska Native (229.5), Hispanic (178.5), NH white (154.5), and NH Asian or Pacific Islander (144.1). Regionally, AAMR was highest in the Midwest (184.6) and lower in non-metropolitan areas (133.3) compared to metropolitan areas (126.3). Conclusion: CKD-related mortality is rising among U.S. adults ≥ 65, especially in non-Hispanic African American males in the Midwest and rural areas. Screening high-risk individuals can enable early detection and lower mortality rates.